Imaginary Consciousness - Sabolius, Kristupas (Problemos, 2007)
The question of time is rarely taken into account while discussing imagination. Phantasy elements are usally analysed and treated as stagnating pictures which do not belong to the chronological flow. This happens, namely because of a frequent intention, also in the philosophical discussion to generalize phantasy defining it as “the unreal of consciousness”. This artice, based on the method of phenomenological description, reveals the temporal structure of imagi nation in action. The latter leads to the greater paradox: the imaginary doesn’t coincide with the egological centre of transcendental subjectivity but is experienced as an uncontrolled poweful function, the Ego prevailing over Otherness whose autonomous character is hidden behind the illusion of the predominating reflective consciousness.
Keywords: imagination, imaginary, phantasy, ego, consciousness